Preparation of Silica-Based Inorganic Capsule Shell via a Novel Emulsion-Sol-Gel Route - Yang, Huazhe; Ji, Yang; Yu, Xiaoming; Zhu, Hao; Zhou, Ling (Asian Journal of Chemistry, 2012)
NH4OH was directly adopted as water phase and catalyst to prepare the silica shell, hexane and Span 80 were respectively adopted as oil phase and emulsifier to prepare water-in-oil emulsion. TEOS was adopted as the silica source, then the silica shell can be obtained through the sol-gel route at the interface of emulsion. Scanning electron microscope and X-ray diffraction were chosen to investigate the morphological and crystallized properties of samples. Results reveal that the morphology of capsule experienced the regular-irregular-regular-irregular transformation and hollow capsule can be obtained when the ratio of water phase to oil phase is 1:6. Furthermore, a schematic model of the experiment is proposed.